Oil palm and rural livelihoods in the Asia-Pacific region: An overview - Cramb, R.; Curry, George (Wiley-Blackwell Publishing Asia, 2012)
The expansion of oil palm cultivation in the Asia-Pacific region in the past half century has engendered a major agro-environmental transformation with significant implications for rural livelihoods. The transformation has taken different forms within and between countries, depending on local contexts, as well as involving an important transnational dimension in terms of regional flows of labour and capital, transboundary and global environmental impacts, and efforts to build international governance structures. This special issue is devoted to seven comparative case studies from across the region to highlight the complexity and diversity of the processes underway. In this introductory paper, we provide an overview of the major economic, social and environmental issues, the different modes of production that have been employed and the varying ways in which land, labour and capital have been mobilised in the region. This overview contextualises the specific studies that follow and emphasises the insights that arise from comparative analysis.